The productivity of political imprisonment: stories from Rhodesia - Alexander, J (Taylor and Francis, 2019)
Political prisons are not only places of violence and silence. They are also productive. Building on recent literature that pays close attention to prisoners’ social and political projects, the article argues that significant, often hidden, aspects of political work take place within the prison, and reach beyond its walls. A focus on the writings and oral histories of political prisoners reveals a remarkable range of imagination and practice within the tight embrace of a hostile state, and shows also its post-colonial reverberations. Through a focus on settler-ruled Rhodesia, I explore the projects and possibilities of nationalists in detention and guerrillas in maximum security prisons, noting their varied and shifting modes of story telling, and the political charge of these stories in the present.